Complete mitogenome of Hainan medaka Oryzias curvinotus (Teleostei: Beloniformes) and transcriptional differences between male and female liver - Zhongduo Wang; Shuisheng Long; Jian Liao; Chengqin Huang; Hairui Zhang; Shunkai Huang; Yanping Zhang; Li Liu; Yusong Guo (Mitochondrial DNA. Part B. Resources, 2017)
In this study, combining the liver transcripts from both sexes by RNA-Seq with DNA sequences by conventional PCRs, we have determined the complete mitogenome of Hainan medaka Oryzias curvinotus collected from the mangrove seawater of the Leizhou Peninsula in tropical South China (Accession no.: KY364884). The mitochondrial genome is 16,676 bp, and its content and structure are highly homologous to those of other teleostean fishes, including 13 protein-coding genes (PCGs), 2 rRNAs, 22 tRNA and 1 control region. Among the PCGs, ATG is used as the initiation codon, except for GTG in COI gene. There are 7 overlapping genes with overlap lengths ranging from 1 to 10 nucleotides (nt), while ten intergenic regions with a total of 66 nt and a maximum interval of 37 nt between tRNAAsn and tRNACys. Moreover, the data from RNA-Seq shows that the significant differences exist in the expression patterns of mitogenomes between male and female.